Positron trapping in BaTiO3 perovskite - Macchi, Carlos Eugenio (2001)
Positron lifetime spectra in BaTiO3 single crystals were measured at temperatures up to 873 K, also at room temperature after quenching from temperatures up to 473 K. The explored temperature range includes the ferroelectric to paraelectric phase transition. The material displays an irreversible behaviour when heated, with anomalies around TC. The temperature dependence of the positron lifetime becomes reversible only after annealing above 550 K. The results suggest modifications of the charge state of non-equilibrium vacancies occurring at moderate temperature and microstructural changes taking place at high temperature. The reversible behaviour of the annealed crystal is consistent with thermally activated positron trap formation.